Threat management priorities for conserving Antarctic biodiversity - Lee, Jasmine R.; Terauds, Aleks; Carwardine, Josie; Shaw, Justine D.; Fuller, Richard A.; Possingham, Hugh P.; Chown, Steven L.; Convey, Peter; Gilbert, Neil; Hughes, Kevin A.; McIvor, Ewan; Robinson, Sharon A.; et al. (PLOS Biology, 2022)
Antarctic terrestrial biodiversity faces multiple threats, from invasive species to climate change. Yet no large-scale assessments of threat management strategies exist. Applying a structured participatory approach, we demonstrate that existing conservation efforts are insufficient in a changing world, estimating that 65% (at best 37%, at worst 97%) of native terrestrial taxa and land-associated seabirds are likely to decline by 2100 under current trajectories. Emperor penguins are identified as the most vulnerable taxon, followed by other seabirds and dry soil nematodes. We find that implementing 10 key threat management strategies in parallel, at an estimated present-day equivalent annual cost of US$23 million, could benefit up to 84% of Antarctic taxa. Climate change is identified as the most pervasive threat to Antarctic biodiversity and influencing global policy to effectively limit climate change is the most beneficial conservation strategy. However, minimising impacts of human activities and improved planning and management of new infrastructure projects are cost-effective and will help to minimise regional threats. Simultaneous global and regional efforts are critical to secure Antarctic biodiversity for future generations.
Keywords: Antarktis; biodiversitet; forvaltning; pingviner

Ant-ICON - ‘Integrated Science to Inform Antarctic and Southern Ocean Conservation’: a new SCAR Scientific Research Programme - Hughes, Kevin A.; Santos, Mercedes; Caccavo, Jilda A.; Chignell, Stephen M.; Gardiner, Natasha B.; Gilbert, Neil; Howkins, Adrian; Van Vuuren, Bettine Jansen; Lee, Jasmine R.; Liggett, Daniela; Lowther, Andrew; Lynch, Heather; et al. (Antarctic Science, 2022)
Antarctic and Southern Ocean environments are facing increasing pressure from multiple threats. The Antarctic Treaty System regularly looks to the Scientific Committee on Antarctic Research (SCAR) for the provision of independent and objective advice based on the best available science to support decision-making, policy development and effective environmental management. The recently approved SCAR Scientific Research Programme Ant-ICON - ‘Integrated Science to Inform Antarctic and Southern Ocean Conservation‘ - facilitates and coordinates high-quality transdisciplinary research to inform the conservation and management of Antarctica, the Southern Ocean and the sub-Antarctic in the context of current and future impacts. The work of Ant-ICON focuses on three research themes examining 1) the current state and future projections of Antarctic systems, species and functions, 2) human impacts and sustainability and 3) socio-ecological approaches to Antarctic and Southern Ocean conservation, and one synthesis theme that seeks to facilitate the provision of timely scientific advice to support effective Antarctic conservation. Research outputs will address the most pressing environmental challenges facing Antarctica and offer high-quality science to policy and advisory bodies including the Antarctic Treaty Consultative Meeting, the Committee for Environmental Protection and the Scientific Committee of the Commission for the Conservation of Antarctic Marine Living Resources.
Keywords: Antarktis; Antarktistraktaten; Sørishavet; forvaltning; human impact; miljøvern